2020
DOI: 10.1111/luts.12350
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clean intermittent catheterization on quality of life of patients with neurogenic lower urinary tract dysfunction due to radical hysterectomy: A cross‐sectional study

Abstract: Aims: We investigated the quality of life (QOL) of a homogenous group of ambulant patients with neurogenic lower urinary tract dysfunction without significant comorbidities to elucidate the impact of clean intermittent catheterization (CIC) on QOL. Methods: The subjects were 71 female patients who underwent radical hysterectomy (RH) without recurrent disease. QOL was cross-sectionally measured with the Short-Form 36-Item Health Survey (SF-36) and King's Health Questionnaire (KHQ). We divided urinary management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…Intermittent catheterization had the greatest impact on GH and VT of all the symptoms analyzed. In an HRQoL study involving patients who developed neurogenic bladder dysfunction after radical hysterectomy, GH, VT, and MH scores were lower in patients on intermittent catheterization than those in patients with spontaneous voiding, despite similar clinical backgrounds other than the use of intermittent catheters ( 29 ). The negative effects of urinary dysfunction on GH, VT, and MH observed in the present study are supported by this report.…”
Section: Discussionmentioning
confidence: 99%
“…Intermittent catheterization had the greatest impact on GH and VT of all the symptoms analyzed. In an HRQoL study involving patients who developed neurogenic bladder dysfunction after radical hysterectomy, GH, VT, and MH scores were lower in patients on intermittent catheterization than those in patients with spontaneous voiding, despite similar clinical backgrounds other than the use of intermittent catheters ( 29 ). The negative effects of urinary dysfunction on GH, VT, and MH observed in the present study are supported by this report.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor staging was performed according to FIGO 2017 criteria into stages I to III. 27 The primary outcome was the time to bladder function recovery, defined as the period from discharge until patients regained autonomous voiding function without symptoms such as urinary frequency, urgency, or dysuria. Urine routine and urine culture results had to be negative, and post-void residual urine volume had to be <100 mL.…”
Section: Outcomementioning
confidence: 99%
“…Continuity of care is also associated with a better QOL, [21][22][23][24][25][26] but the present study was not designed to be able to examine the independent contribution of self-IC and continuity of care. Sekido et al 27 showed that although the short-term QOL of patients with IC after hysterectomy was poorer than in patients with spontaneous voiding, the difference disappeared with time, and the patients with IC ultimately had a QOL similar to those with spontaneous voiding. Of course, the early recovery of bladder function and independence from the urinary catheter are major factors contributing to improving the patient's QOL.…”
mentioning
confidence: 99%
“…Extensive research attests to the manifold benefits of CIC, including a reduced incidence of urinary tract infections, prevention of urethral and bladder injuries and preservation of optimal bladder and kidney functions (Biaziolo et al, 2017;Faleiros et al, 2018;Lamin and Newman, 2016). Moreover, empowering individuals to take charge of their bladder functions through CIC fosters a profound sense of independence, consequently bolstering their self-assurance and overall quality of life (Goldstine et al, 2019;Sekido et al, 2021;Silva et al, 2017).The implementation of CIC requires specialised psychomotor skills. Despite its numerous benefits, improper application can lead to urethral injuries and infections, undermining patient confidence in self-care.…”
mentioning
confidence: 99%